Search for technicolor particles produced in association with a W Boson at CDF. - Aaltonen, T; Adelman, J; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; Artikov, A; et al. (2010)
We present a search for the technicolor particles rhoT and pi_{T} in the process pp-->rhoT-->WpiT at a center of mass energy of sqrt[s]=1.96 TeV. The search uses a data sample corresponding to approximately 1.9 fb{-1} of integrated luminosity accumulated by the CDF II detector at the Fermilab Tevatron. The event signature we consider is W-->lnu and piT-->bb, bc or bu depending on the piT charge. We select events with a single high-pT electron or muon, large missing transverse energy, and two jets. Jets corresponding to bottom quarks are identified with multiple b-tagging algorithms. The observed number of events and the invariant mass distributions are consistent with the standard model background expectations, and we exclude a region at 95% confidence level in the rhoT-piT mass plane. As a result, a large fraction of the region m(rhoT)=180-250 GeV/c{2} and m(piT)=95-145 GeV/c{2} is excluded.